Pendampingan Ideologi Aswaja Berbasis Literasi Digital Membangun Militansi Moderat Kader Ansor Banser Pagar Nusa Lampung - Wakib Kurniawan; Resti Fatma Ayuningsih; Safiratun Najah (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2026)
The rise of ideological challenges and the spread of extreme religious views in the digital era have significantly affected cadre development within GP Ansor, Banser, and Pagar Nusa. This study employed a Participatory Action Research (PAR) approach, involving cadres in Central Lampung as active partners throughout all stages. Data were collected through participatory observation, in-depth interviews, Focus Group Discussions (FGD), and documentation. Data analysis followed an interactive model, including data reduction, presentation, and reflective conclusion drawing. The PAR approach emphasizes collaboration between academics and the community, positioning cadres not merely as objects but as active agents of social transformation. The program focused on strengthening Aswaja ideology integrated with digital literacy to address ideological and technological challenges. The results indicate improved understanding and skills among cadres, while also contributing to the development of a contextual, sustainable, and community-based ideological mentoring model that has the potential to be replicated across other NU branches in Indonesia.